Screening of Active Compounds of Baeckea frutescens Using Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) and Its Saponification Process - Aina Irdina Aizo; Liyana Amalina Adnan; Rahayu Ahmad; Ahmad Hakimi Shaffie; Nurdalila A’wani Abdul Aziz (Malaysian Institute of Chemistry (Institut Kimia Malaysia), 2024)
Indexed by Scopus